Serangan Hama Putih Palsu (Cnaphalocrocis Medinalis) (Guenee) dan Penampilan Agronomik pada Beberapa Varietas Padi - Suprapto Suprapto; Bariot Hafif (Politeknik Negeri Lampung., 2012)
The study of leaffolder (Cnaphalocrocis medinalis) attack and the agronomic performance of new rice varieties Inpari 13 and Cigelis has been done by AIAT Lampung on dry season (MK) May 2011 to August 2011 at Wonosari village, Sub distric Pekalongan, East Lampung.The study aims to obtain new varieties of high production and tolerant to pests and diseases.The study was conducted by randomized block design, consisting of three treatment rice varieties as Inpari 13, Cigelis and Ciherang as conttrol, were repeated 3 time.The size plots 6 m x 5 m, rice is planted moving, spacing 20 cm x 25 cm, 23 days old seedlings were planted, the number of seedlings planted 1-3 stems per clump, fertilizing 250 kg Urea + 250 kg NPK and 7500 kg of compost and 500 cc ZPT per hectare. Observations on 10 samples per plot clumps were determined randomly in the middle plants of the clump within 10 row plants from the edge of plot lines. Which observed were height plant, number of tillers and productive tillers per panicle, leaffolder (Cnaphalocrocis medinalis) attack at 35 days after planting, dry grain production (GKP), grain fill and empty grains per panicle. Data were analyzed by DMRT test at 5% level difference. The results showed that leaffolder pests attacking on rice varieties Inpari 13, Cigelis and Ciherang since planted up to 35 days after planting with varying levels of damage to each variety. Leaffolder pests highest attack on Ciherang varieties (34.28%) followed Inpari 13 (32.29%) and lowest Cigelis (13.33%). Number of rice seedlings at the age of 35 days highest Inpari 13 and Ciherang, the number of tillers in the two varieties are almost the same, were respectivelly 11.80 and 11.81 stems per clump and the lowest Cigelis 10.83 stems per clump.The number of productive tillers varieties Inpari 13, Cigelis and Ciherang relatively the same, were 14.6 stems (98.18%), 15.0 stems (97.40%) and 15.0 stems (97.40%) respectivelly. The number of grains and pithy grains per panicle highest Inpari 13 varieties of 134.33 grains (grains pithy 128.73 grains), Cigelis 114.13 grains (grains pithy 110.73 grains) and lowest Ciherang 90.73 grains (grains pithy 87.53 grains). The productivity of Suprapto dan Bariot Hafif : Serangan Hama Putih Palsu (Cnaphalocrocis Medinalis)... Volume 12, Nomor 1, Januari 2012 37 dry grain harvest (GKP) highest in varieties Inpari 13 (6400 kg / ha), followed Cigelis (6080 kg / ha) and lowest Ciherang (4480 kg / ha).Keywords : Leaffolder, rice, varieties, attack, agronomic, production